Legalitas Perkawinan yang Tidak Tercatat pada Masyarakat Pinrang ( Analisis Perma Nomor 1 Tahun 2015 tentang Pelayanan Terpadu Pencatatan Nikah) - Agus Muchsin; Rukiah; Muhammad Sabir (DIKTUM: Jurnal Syariah dan Hukum, 2019)
Marriage is a unique event because marriage is a way of gluing the knot of a family. Sociologically, the Bugis Pinrang community is obedient and obedient to the law. However, the application of marriage records has not been carried out optimally. Because there are still some couples who have not registered their marriages. This habit is proof that the legal culture has not been built to its full potential. Non-recorded marriages will have a legal impact on the child and wife. Unregistered marriages should need legal protection, not to be left without providing a solution. The form of protection was outlined in technical form by providing an opportunity to carry out the marriage certificate on the marriage which had been carried out according to the Islamic Shari'a, but was not recorded by authorized employees. Marriage rules are intended for certain things as contained in article 7 paragraph (3) KHI. The existence of this Article provides legal protection by giving the opportunity to submit a marriage certificate application. So that marriages that have not been recorded, can be recorded and recognized administratively, so that they become marriages that are formal or legal juridically.